Modification of 3D materials based on chitosan and collagen blends by sodium alginate. (21st November 2016) - Sionkowska, A.; Kaczmarek, B.
ABSTRACT: The aim of this work was to study the properties of chitosan/collagen blend modified by sodium alginate. 3D composites of chitosan/collagen blend were prepared by freeze drying technique. The results showed that sodium alginate modified the properties of the 3D composite of chitosan/collagen blends. The porosity decreased and the mechanical properties were improved. Mechanical parameters increased with an increasing amount of sodium alginate in chitosan/collagen composite. Materials after cross-linking by sodium alginate can be used in medical applications to produce implants or wound dressings.